(untitled) (Praxis Educativa, 2020)
This chapter is divided into three somewhat disjointed parts. I have not tried to create artificial transitions. The first section is an edited transcript of only part of what actually happened at the podium ¿can the subaltern speak?. The second part is something like a prepared paper. The third part is answers to a series of questions generated: how can the humanities produce the intuitions of democracy in the broadest possible race, class- and gender-diversified sector of the population? What is it to teach the humanities? What is the in-built aporia of democracy? How do we confront the inevitable corporatisation of the entire education system? What is the role of the curriculum? What is the relationship between class, race, and liberal education in our countries? What is the relationship between a will to social justice and enforcement? What is it to interpret a history of violence and use it without accusation or excuse within the broadest interpretation of the academy? Why is national liberation not a revolution? How do we combat the anthropocene?